The excess-voltage protection of electric traction networks of direct current. The methodology of choosing surge protection device - Kim, Ye. D.; Sychenko, V. H. (Science and Transport Progress, 2011)
The article is dealt with the selecting methodology of overvoltage arresters for DC traction line.